If it's not what You are looking for type in the equation solver your own equation and let us solve it.
96=-4(8-4x)
We move all terms to the left:
96-(-4(8-4x))=0
We add all the numbers together, and all the variables
-(-4(-4x+8))+96=0
We calculate terms in parentheses: -(-4(-4x+8)), so:We get rid of parentheses
-4(-4x+8)
We multiply parentheses
16x-32
Back to the equation:
-(16x-32)
-16x+32+96=0
We add all the numbers together, and all the variables
-16x+128=0
We move all terms containing x to the left, all other terms to the right
-16x=-128
x=-128/-16
x=+8
| 5x-3+2x=3x+17 | | 14v+2=30 | | (2x+7)=(4x−17) | | -53-y/7=61 | | 2n+5+3n=4-6n+8 | | 0=v4-1 | | 3(x+2)-5=5x-2 | | 7y-3y-10=63.48 | | 7x-22+2x+38=62 | | 0.2x-12.4+1.6x+4.4=28 | | -10+10r=2r+4+2 | | (2x+5)/3(4-x)/4=3/4 | | z/5-26=-4 | | 7/19=n/19 | | 3-t=3/5 | | -15-3x=5x-2x | | 7x-22+2x+38=124 | | 6n-7=3n+8 | | -3/5+z=2/4 | | 2/5(x-17)=26 | | 12+5x=16+4x | | x+9-2x+7x-3+4=46 | | 8z-7=-21+5z | | 5+45=-5(9x-10) | | 15y+26=116 | | 7x-22+2x+38=55 | | 4m-3=2m-9 | | -34k-11=23 | | -5(2x-1)=-35 | | 4/9y-1=25 | | c/24=-3 | | 3g+2g=18 |